Enhancing mechanical properties and crack resistance of earth-sand building materials through alfa fiber reinforcement: An experimental investigation - Sadouri, Reda; Kebir, Hocine; Benyoucef, Mustafa (Građevinski materijali i konstrukcije, 2024)
This paper investigates enhancing the mechanical properties and crack resistance of earth-sand building materials by incorporating Alfa fibers, derived from the Alfa plant. Earth-based construction materials, known for their sustainability, face challenges in mechanical performance and cracking. The study explores a composite of earth (60 wt%) and sand (40 wt%) reinforced with Alfa fibers of varying lengths and rates. Tensile strength and water absorption of the fibers were assessed, and prismatic specimens (40x40x160 mm3 ) with different cutting lengths were tested. Results inform the potential of Alfa fibers for improving earth-based material performance. Incorporating 2% wt of Alfa fibers reduced the unit weight of the composite from 1849 kg/m3 to 1632 kg/m3 , resulting in a slight material weight decrease. Compared to unreinforced adobe specimens, fibrous samples exhibited lower linear shrinkage rates and improved mechanical behavior, with 2% wt of 3 cm fibers showing optimal performance. The fibers effectively impeded crack propagation, with both length and content influencing crack attenuation. However, microstructural observation revealed poor fiber/matrix adhesion, negatively impacting adobe specimen compactness despite enhanced mechanical properties.